2020
DOI: 10.1177/0266666920965642
|View full text |Cite
|
Sign up to set email alerts
|

Reading habits of generation Z students in Pakistan: Is it time to re-examine school library services?

Abstract: Quality academic achievement is based on the development of good reading skills. Generally, reading is important for students to cope up with the evolving world of knowledge. Information and Communication Technologies (ICTs) have vastly influenced the reading practices of students. The younger generation of the information age spends most of their time in front of screens. Due to these drastic changes in the fabric of reading, generation Z is more likely to adopt e-reading. Therefore, an empirical investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…This is in accordance with research from Olagbaju and Popola where they use audio-visual media in teaching materials. The results showed a significant difference in the treatment of students' interest and achievement in the reading comprehension (Mushtaq et al, 2021;Olagbaju & Popoola, 2020). Research conducted by Khorasani et.al.…”
Section: Questionsmentioning
confidence: 78%
“…This is in accordance with research from Olagbaju and Popola where they use audio-visual media in teaching materials. The results showed a significant difference in the treatment of students' interest and achievement in the reading comprehension (Mushtaq et al, 2021;Olagbaju & Popoola, 2020). Research conducted by Khorasani et.al.…”
Section: Questionsmentioning
confidence: 78%
“…Mushtaq et al [8] note that ICT have had a significant impact on the reading practices of 21st-century learners. Generation Z spend a lot of time in front of screens, and so they are often attracted to this new reading format, with which they are very familiar.…”
Section: Methodologies For Encouraging Readingmentioning
confidence: 99%
“…On the other hand, quality education has its foundations in the good development of reading skills since they are fundamental to facing the knowledge society in which we find ourselves [7,8]. Sánchez-García [9] agrees that the benefits of reading go beyond the school environment, as reading favours social integration and the integral education of the individual.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Before the pandemic, many institutions were run via a traditional face-to-face didactic model of learning, especially in low income settings. 7 Before the pandemic, a study performed on undergraduate engineering students found an e-laboratory fostered more active learning and enabled students to take more responsibility for their learning when compared to their traditional physical laboratory sessions. 8 A review conducted in 2020 found that higher education institutions face several challenges related to asynchronous/ synchronous learning integration.…”
Section: Introductionmentioning
confidence: 99%